Hubungan Antara Dukungan Keluarga Dengan Keaktifan Kunjungan Lansia Ke Posyandu Lansia Dusun Gampingan Desa Wonokerto Kecamatan Bantur Kabupaten Malang - Anandita Rachma Nur Safitri; Achmad Dafir Firdaus; Ratna Wulandari (Jurnal Keperawatan Muhammadiyah, 2026)
Objective: The epidemiological transition from infectious diseases to non-communicable diseases (NCDs) has increased the risk of elderly individuals experiencing multiple pathological conditions. Family support is one of the important factors that can influence the elderly in carrying out health care and health promotion efforts, one of which is routine attendance at the Elderly Integrated Health Service Post (Posyandu Lansia). This study aimed to determine the relationship between family support and the activeness of elderly visits at the Posyandu Lansia in Gampingan Hamlet, Wonokerto Village, Bantur District, Malang Regency. Methods: This research employed a correlational analytic method with a retrospective approach. The study population consisted of 58 elderly individuals who met the research criteria, with total sampling used as the sampling technique. The research instruments included a questionnaire and a register sheet of elderly visit data for participation in the Posyandu Lansia Results: The results showed that half of the respondents were less active in attending the Posyandu, accounting for 50% (29 individuals). Data analysis using the Spearman Rho test indicated a significant relationship between family support and the activeness of elderly visits to the Posyandu Lansia in Gampingan Hamlet, Wonokerto Village, Bantur District, Malang Regency, with a very strong correlation (p-value = 0.000) and a correlation coefficient (r) of +0.841. The results demonstrated that the p-value (0.000) was less than the significance level (0.05), Conclusion: In conclusion indicating that there is a significant relationship between family support and the activeness of elderly visits to the Posyandu Lansia in Gampingan Hamlet, Wonokerto Village, Bantur District, Malang Regency